2014
DOI: 10.1155/2014/803972
|View full text |Cite
|
Sign up to set email alerts
|

3D Blade Hydraulic Design Method of the Rotodynamic Multiphase Pump Impeller and Performance Research

Abstract: A hydraulic design method of three-dimensional blade was presented to design the blades of the rotodynamic multiphase pump. Numerical simulations and bench test were conducted to investigate the performance of the example impeller designed by the presented method. The results obtained from the bench test were in good agreement with the simulation results, which indicated the reasonability of the simulation. The distributions of pressure and gas volume fraction were analyzed and the results showed that the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Because of its computational efficiency and acceptable computational accuracy for steady simulation, the external characteristics of pumps, such as efficiency and head, are predicted by steady simulation (Kim et al, 2015;Tan et al, 2014;Zhang et al, 2014). To verify the reliability of the numerical methods adopted in this study, the inlet of computational domain was set as total mass flow rate and corresponding void fraction of the medium; the diameter of gas bubble in two-phase flow was given 0.4 mm according to the experimental value; while at the outlet, the static pressure was specified.…”
Section: Steady Simulationmentioning
confidence: 99%
“…Because of its computational efficiency and acceptable computational accuracy for steady simulation, the external characteristics of pumps, such as efficiency and head, are predicted by steady simulation (Kim et al, 2015;Tan et al, 2014;Zhang et al, 2014). To verify the reliability of the numerical methods adopted in this study, the inlet of computational domain was set as total mass flow rate and corresponding void fraction of the medium; the diameter of gas bubble in two-phase flow was given 0.4 mm according to the experimental value; while at the outlet, the static pressure was specified.…”
Section: Steady Simulationmentioning
confidence: 99%
“…According to this method, the geometry of impeller was determined by specified velocity torque distribution. The three-dimensional hydraulic method was also employed by Zhang et al [25], and it was effective to suppress the performance decline under large flow rate. For rotodynamic multiphase pump, a diffuser is always equipped after an impeller to recover the kinetic energy from fluid and adjust the flow direction.…”
Section: Introductionmentioning
confidence: 99%
“…After the compression at the first stage, q i reduces from 10.53 to 13.69 per cent and β i reduces from 10.48 to 13.62 per cent when n changes from 1800 to 2700 r/min respectively. It can be observed that the extent of q i and β i reduction is larger with an increase in n. Based on the work of Zhang et al . (2014b), the performance of multiphase pump can be improved with an increase in n .…”
Section: Analysis Of Flow Parametersmentioning
confidence: 97%